(untitled) (International Journal of Engineering and Computer Science, 2017)
Ad hoc networking allows mobile devices to establish communication path without having any central infrastructure. There is no central infrastructure and the mobile devices moves randomly which gives rise to various kinds of problems such as routing and security. In this dissertation the problem of routing is considered. Because of highly dynamic and distributed nature of nodes routing is one of the key issues in MANETs. There are three main classes of routing protocols are proactive, reactive and hybrid.In this paper an effort has been made to compare the performance of two reactive routing protocols- AODV (Ad-hoc on-demand distance vector) and DSR (Dynamic source routing). AODV and DSR are reactive protocols where each node sends routing packets only when communication is needed. Both the protocols have different mechanisms which lead to significant performance differentials. The protocols are analyzed using four performance metrics- packet delivery ratio, throughput, routing load and end-to-end delay by varying number of nodes, pause time and simulation time